2020
DOI: 10.1177/0003489420950381
|View full text |Cite
|
Sign up to set email alerts
|

‘Mini-Microsuture Technique’ for Phonosurgery: A New Simplified Method

Abstract: Introduction: Phonomicrolaryngeal surgery involves the surgical treatment of benign disorders of the vocal folds. Postoperative scar tissue in vocal fold mucosa is undesired because mucosal hypodynamia may lead to prolonged impairment in voice quality. This study aims to present and share the outcomes of a new endolaryngeal suture technique. Methods: This study consists of patients who underwent vocal fold surgery followed by endolaryngeal microscopic suturation with a technique that we call the “mini-microsut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The atrophic mucosa underlying the sulcus base was prepared and excised while preserving the vocal ligament. Mini-microsuture technique 15 using 8/0 vicryl was used to suture the medial and lateral edges of the bridge to the mucosa until it was observed that no mucosal gap was left (Supplemental Video 1 and Figures 1 and 2). Afterward, 10 cc blood was drawn from the patient to harvest autologous platelet-rich plasma, which was applied submucosally to facilitate mucosal healing and the operation was ended.…”
Section: Methodsmentioning
confidence: 99%
“…The atrophic mucosa underlying the sulcus base was prepared and excised while preserving the vocal ligament. Mini-microsuture technique 15 using 8/0 vicryl was used to suture the medial and lateral edges of the bridge to the mucosa until it was observed that no mucosal gap was left (Supplemental Video 1 and Figures 1 and 2). Afterward, 10 cc blood was drawn from the patient to harvest autologous platelet-rich plasma, which was applied submucosally to facilitate mucosal healing and the operation was ended.…”
Section: Methodsmentioning
confidence: 99%